Step ![1](https://tex.z-dn.net/?f=%201%20)
<u>Find the slope of the given line</u>
Let
![A(-3,2)\ B(2,-1)](https://tex.z-dn.net/?f=%20A%28-3%2C2%29%5C%20B%282%2C-1%29%20%20)
slope mAB is equal to
![mAB=\frac{(y2-y1)}{(x2-x1)} \\ \\ mAB=\frac{(-1-2)}{(2+3)} \\ \\ mAB=-\frac{3}{5}](https://tex.z-dn.net/?f=%20mAB%3D%5Cfrac%7B%28y2-y1%29%7D%7B%28x2-x1%29%7D%20%5C%5C%20%5C%5C%20mAB%3D%5Cfrac%7B%28-1-2%29%7D%7B%282%2B3%29%7D%20%5C%5C%20%5C%5C%20mAB%3D-%5Cfrac%7B3%7D%7B5%7D%20%20)
Step ![2](https://tex.z-dn.net/?f=%202%20)
<u>Find the slope of the line that is perpendicular to the given line</u>
Let
CD ------> the line that is perpendicular to the given line
we know that
If two lines are perpendicular, then the product of their slopes is equal to ![-1](https://tex.z-dn.net/?f=%20-1%20)
so
![mAB*mCD=-1\\ mAB=-\frac{3}{5} \\ mCD=-\frac{1}{mAB} \\ mCD=\frac{5}{3}](https://tex.z-dn.net/?f=%20mAB%2AmCD%3D-1%5C%5C%20mAB%3D-%5Cfrac%7B3%7D%7B5%7D%20%5C%5C%20mCD%3D-%5Cfrac%7B1%7D%7BmAB%7D%20%5C%5C%20mCD%3D%5Cfrac%7B5%7D%7B3%7D%20%20)
Step ![3](https://tex.z-dn.net/?f=%203%20)
<u>Find the equation of the line with mCD and the point (3,0)</u>
we know that
the equation of the line in the form point-slope is equal to
![y-y1=m(x-x1)\\\\ y-0=\frac{5}{3} *(x-3)\\\\ y=\frac{5}{3} x-5](https://tex.z-dn.net/?f=%20y-y1%3Dm%28x-x1%29%5C%5C%5C%5C%20y-0%3D%5Cfrac%7B5%7D%7B3%7D%20%2A%28x-3%29%5C%5C%5C%5C%20y%3D%5Cfrac%7B5%7D%7B3%7D%20x-5%20%20%20)
Multiply by
both sides
![3y=5x-15](https://tex.z-dn.net/?f=%203y%3D5x-15%20)
![5x-3y=15](https://tex.z-dn.net/?f=%205x-3y%3D15%20)
therefore
the answer is
the equation of the line that is perpendicular to the given line is the equation ![5x-3y=15](https://tex.z-dn.net/?f=%205x-3y%3D15%20)